Bioactivity of the Ferns of Moorea, French Polynesia: Exploring the bioactivity and traditional use of ferns in Moorea, French Polynesia (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The legitimacy of this article is to provide a head start for a reasonable future evaluation of clinical ethnobotany and bioactivity of pteridophytes in Moorea, French Polynesia. Pteridophytes join a small part of the Moorish pharmacopoeia although it is a wonderfully abundant commodity on this tropical island. Important open information on the phytochemistry, bioactivity and clinical ethnobotany of the generally gigantic number of genera found on Moorea is collected here. It contains information from interviews with Moorish healers and more organized people, compiled in 2005.